2021
DOI: 10.1002/mds.28651
|View full text |Cite
|
Sign up to set email alerts
|

RT‐QuIC Detection of Pathological α‐Synuclein in Skin Punches of Patients with Lewy Body Disease

Abstract: Background: Evidence suggests that skin represents a suitable matrix for demonstrating α-synuclein oligomers as a diagnostic biomarker for Lewy body disease. Objective: The objective of this study was to evaluate the diagnostic performance of skin α-syn real-time quaking-induced conversion assay in patients with Lewy body disease. Methods: We analyzed skin punches taken in vitam (n = 69) or postmortem (n = 49) from patients with PD, dementia with Lew bodies (DLB), incidental Lewy body pathology, and neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 22 publications
1
75
1
Order By: Relevance
“…Neuropathology was available for only two patients, one with MSA as described above, and another (#3076) who had mixed Lewy body and Alzheimer pathology and that was detected as αSyn-SAA-positive by all three groups. There have been several important studies by other groups of αSyn-SAA of CSF [ 6 , 24 , 45 ] or skin [ 12 , 17 , 45 ] of autopsy-confirmed patient cohorts, with comparable diagnostic performance. We had sought to validate SAAs within an early PD cohort, which has correspondingly limited neuropathologic data from autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathology was available for only two patients, one with MSA as described above, and another (#3076) who had mixed Lewy body and Alzheimer pathology and that was detected as αSyn-SAA-positive by all three groups. There have been several important studies by other groups of αSyn-SAA of CSF [ 6 , 24 , 45 ] or skin [ 12 , 17 , 45 ] of autopsy-confirmed patient cohorts, with comparable diagnostic performance. We had sought to validate SAAs within an early PD cohort, which has correspondingly limited neuropathologic data from autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…A potential biochemical marker for detecting DLB is α-synuclein. RT-QuIC measures that detect α-synuclein aggregates capable of seeding fibril formation have high accuracy when measured in CSF or skin biopsy samples but are not yet detectable in plasma [ 10 , 24 , 34 ]. Unfortunately, no specific biochemical marker for HS or LATE is available at present.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, researchers published findings showing that skin biopsies from proximal (cervical) and distal (thigh and distal leg) sites demonstrated phosphorylated α-synuclein in the cutaneous nerves of individuals with DLB ( n = 18) versus individuals with other dementias ( n = 23) and healthy controls ( n = 25). 41 Using skin biopsies to identify pathological α-synuclein continues to be an area of active research in DLB, PD, and other synucleinopathies, 42 45 including prodromal states (RBD). 44 Immunofluorescence and RT-QuIC approaches to detecting α-synuclein in skin biopsies show comparable efficacy 46 and one study showed similar diagnostic accuracy when comparing RT-QuIC assays using CSF versus skin samples.…”
Section: Biomarkersmentioning
confidence: 99%
“… 44 Immunofluorescence and RT-QuIC approaches to detecting α-synuclein in skin biopsies show comparable efficacy 46 and one study showed similar diagnostic accuracy when comparing RT-QuIC assays using CSF versus skin samples. 45 Commercial testing for synucleinopathies using skin punch biopsies is now available in the United States. As with CSF α-synuclein testing, the role that skin biopsy plays in routine clinical diagnosis of DLB is yet to be established.…”
Section: Biomarkersmentioning
confidence: 99%